Evolução cariotípica de roedores sigmodontinae na América do Sul - Mesquita, Higor Luiz Araújo de (2019)
Studies on the evolution of the 2n character were made in mammals and the presence of certain tendencies in the trait is noticed. Some articles suggest that the character evolves under selective force acting for the reduction of its value and others show a tendency towards its increase. The variability of this trait in rodents is remarkable, being not only interspecific but also intraspecific. This clade is also notable for being the most specious of all mammals. Despite this variability and presumed tendencies present in the group, it was not tested whether there is a targeting of natural selection of this trait or if the phylogeny can explain its values. So it’s therefore necessary to answer questions such as the possible existence of a tendency of related species to present trace values more similar than expected randomly in the phylogeny, and if this trait evolves predominantly by neutral evolution or by natural selection. We use comparative phylogenetic methods to answer such questions because they use phylogenetic relationships as the basis for statistically analyzing the cited patterns. A phylogenetic signal test was performed and an attempt was made to understand which evolutionary model (Brownian motion or Ornstein-Uhlenbeck) best explains the evolution of this trait in the studied clade. A survey of all rodent species of the subfamily Sigmodontinae of South America and their respective karyotypes was performed, resulting in 235 diploid numbers of the 384 rodent species of the subfamily Sigmodontinae occurring on the South American continent. We set up a supertree tree of Sigmodontinae type through topologies of trees of already published articles resulting in a tree with 303 terminal taxa and we use a dated tree for the analyzes. Pagel's lambda was significant and detected the presence of a phylogenetic signal in the evolution of the diploid number in Sigmodontinae. The best evolution model selected by AIC was the Brownian motion. The work contributes to the understanding about the evolution of the trait of the clade and tries to answer, with new tools, questions already asked but never completed.